Antibody responses to respiratory coronavirus infections of cattle during shipping fever pathogenesis - X. Q. Lin; K. L. O’Reilly; J. Storz; C. W. Purdy; R. W. Loan (Archives of Virology, 2000)

Differences in size and growth rates of male and female migrating Japanese eels in Pearl River, China - W. N. Tzeng; H. R. Lin; C. H. Wang; S. N. Xu (Journal of Fish Biology, 2000)
The Sr/Ca ratios in otoliths of silver Japanese eels Anguilla japonica , in Pearl River, China, indicated that both sexes did not stay in brackish water and grew in fresh water from the glass eel stage until spawning migration. This did not support the hypothesis that females tended to distribute upstream and males might be restricted to estuaries. The back‐calculated total length of males at glass eel stage was not significantly different from that of females, indicating that the hypothesis that small glass eels became males and larger ones became females may not be true. The mean (±S.D.) age and total length of males at migration were 6·4±1·6 years and 48·3±4·5 cm, which were significantly smaller than for females, 8·3±1·6 years and 61·4±4·1 cm. The age of migration was related inversely to growth rate for both sexes. Growth parameters of the von Bertalanffy growth equation were K =0·21 cm year°1, L ∞ =55·7 cm and t o =‐0·55 year for males and K =0·14 cm year −1 , L ∞ =77·5 cm and t o =‐0·60 year for females. The difference in asymptotic length ( L ∞ ) between males and females may be because females postpone migration to achieve larger size for maximizing reproductive success.

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)